2018
DOI: 10.1186/s12875-018-0748-z
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome and its prevalence in primary care nursing: a systematic review and meta-analysis

Abstract: Backgroundburnout syndrome is a significant problem in nursing professionals. Although, the unit where nurses work may influence burnout development. Nurses that work in primary care units may be at higher risk of burnout. The aim of the study was to estimate the prevalence of emotional exhaustion, depersonalization and low personal accomplishment in primary care nurses.MethodsWe performed a meta-analysis. We searched Pubmed, CINAHL, Scopus, Scielo, Proquest, CUIDEN and LILACS databases up to September 2017 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
100
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 35 publications
9
100
8
2
Order By: Relevance
“…The healthcare environment can have a negative impact on workers, due to factors such as shift working, stress, the burdens of care, peer relationships and performance targets, together with high levels of emotional demand that may cause anxiety, frustration, stress, depression and burnout (Johnson et al, ; Lee, Chiang, & Kuo, ; Maslach, Schaufeli, & Leiter, ; Salvarani et al, ). This situation can provoke major problems for healthcare personnel in general and for nurses in particular (Cañadas‐De la Fuente et al, ), who often present high levels of burnout (Akman, Ozturk, Bektas, Ayar, & Armstrong, ; Gómez‐Urquiza et al, ; Molina‐Praena et al, ; Monsalve‐Reyes et al, ; Pradas‐Hernández et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The healthcare environment can have a negative impact on workers, due to factors such as shift working, stress, the burdens of care, peer relationships and performance targets, together with high levels of emotional demand that may cause anxiety, frustration, stress, depression and burnout (Johnson et al, ; Lee, Chiang, & Kuo, ; Maslach, Schaufeli, & Leiter, ; Salvarani et al, ). This situation can provoke major problems for healthcare personnel in general and for nurses in particular (Cañadas‐De la Fuente et al, ), who often present high levels of burnout (Akman, Ozturk, Bektas, Ayar, & Armstrong, ; Gómez‐Urquiza et al, ; Molina‐Praena et al, ; Monsalve‐Reyes et al, ; Pradas‐Hernández et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Also important are sociodemographic variables such as being male, single, and not having children (Cañadas‐De la Fuente et al ; Gómez‐Urquiza et al ) or personality factors like neuroticism (De la Fuente‐Solana et al ) make nurses more prone to burnout. Most previous studies in this field have been conducted with samples of nurses working in different units, but there are significant differences in the day‐to‐day experiences of nurses according to the medical area in which they are working, for example in accident and emergency (Albendín et al ) or in primary care (Monsalve‐Reyes et al ). Differences between one area and another can be an important factor in the development of burnout.…”
Section: Introductionmentioning
confidence: 99%
“…In workplaces where burnout levels are high, there is increased turnover of professionals [8]. Nurses burnout has been studied in several clinical setting, with different results being reported [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Monsalve-Reyes et al [9], in a systematic review about burnout in nurses working in primary care, found that emotional exhaustion and low personal accomplishment are very common in this clinical field. They stated that primary care nurses are a group at high risk of burnout.…”
Section: Introductionmentioning
confidence: 99%